Profesionalisme dan Kepuasan Kerja Terhadap Kinerja Auditor - Mohammad Ali Sartono (Universitas La Tansa Mashiro, 2014)
Nowadays, public accounting firm is an organization a lot of challenges and problems at the same time, as business competition is very tough. The growing number of professional auditors who work in the organization, the professionalism of auditors and job satisfaction on performance. A quantitative analysis was used to identify current auditor performance. Its approach was used to explain the effect of proffesionalism and job satisfaction on auditor performance. In addition to it, activities which are related to proffesionalism, job satisfaction, and auditor performance are described.